THE ESTIMATION OF CARCASS TRAITS OF BALI BULLS USING ULTRASOUND - Sri Rachma, A.B.; Harada, H. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
A study was conducted to collect information on Bali bulls carcass traits estimation as one of theselection criteria using ultrasound. Ultrasonic estimation of carcass traits such as M. longissimusthoracis area (MLTA), Subcutaneous Fat Thickness (SFT), Inter Muscular Fat Thickness (IMFT), RibThickness (RT) and Beef Marbling Score (BMS) were obtained from 92 head of bulls at Barru districtand 74 head of bulls at Bone district, South Sulawesi, Indonesia. The carcass traits estimation werescanned between the 6th - 7th ribs using ultrasound. The ultrasound is made of Fujihira Super-Eye FHK,Co. Meat. Ltd. with B-Mode and electronic linear probe, which used frequency of 2 MHz. The carcasstraits estimation photos were printed by video-copy machine (Aloka Co. Ltd., SSZ-300S). The dataobtained were analyzed using basic statistic and was discussed descriptively. The averages of all carcasstraits estimation of the Bali bull at Bone district at 12, 18 and 24 months of ages were higher than thoseat Barru district. The MLTA estimation of Bali bulls at Bone and Barru districts were 18.0 cm2, 24.3cm2, 23.8 cm2 Vs 16.6 cm2, 18.5 cm2, 23.3 cm2, respectively; the BMS estimated were 0.14, 0.24 and0.20 Vs 0.00, 0.15 and 0.17, respectively; the SFT estimation were 0.26 mm, 0.33 mm, 0.34 mm Vs0.28 mm, 0.26 mm, 0.34 mm, respectively; the IMFT estimation were 1.13 mm, 1.24 mm, 1.31 mm Vs0.97 mm, 1.06 mm, 1.14 mm, respectively; the RT estimation were 2.04 mm, 2.52 mm, 2.72 mm Vs1.19 mm, 2.12 mm, 2.30 mm, respectively. The growth of MLTA, SFT, IMFT, RT and BMS of thebulls of Bali cattle at the 12, 18 and 24 months of age were not reaching the optimally performances,yet. Therefore the selection process of the bulls of Bali cattle to be candidate of sire based on theestimation of carcass traits should be done after since 4 years of age.